2014
DOI: 10.1002/nag.2282
|View full text |Cite
|
Sign up to set email alerts
|

A bond failure criterion for DEM simulations of cemented geomaterials considering variable bond thickness

Abstract: SUMMARY A series of micromechanical tests were conducted to investigate the bond failure criterion of bonded granules considering the effect of bond thickness, with the aim of enhancing the bond contact model used in the distinct element simulations of cemented geomaterials. The granules were idealized in a two‐dimensional context as one pair of aluminum rods bonded by resin epoxy or cement. The mechanical responses of nearly 500 rod pairs were tested under different loading paths to attain the yield loads of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
5
17
0
Order By: Relevance
“…It has been reported that both the mechanical behavior and the bond strength are different for different bond models, which was concluded from the experimental data obtained for two aluminium rods bonded by cement with a fixed bond width . As a first step in simulation analyses considering the effect of bond model, Jiang et al proposed a new bond failure criterion for DEM simulations of bonded granulates. Thereafter, Jiang et al performed loading tests on a couple of aluminium rods glued together by cement with various values of width and thickness and proposed a rigorous failure criterion for the inter‐particle bonding.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that both the mechanical behavior and the bond strength are different for different bond models, which was concluded from the experimental data obtained for two aluminium rods bonded by cement with a fixed bond width . As a first step in simulation analyses considering the effect of bond model, Jiang et al proposed a new bond failure criterion for DEM simulations of bonded granulates. Thereafter, Jiang et al performed loading tests on a couple of aluminium rods glued together by cement with various values of width and thickness and proposed a rigorous failure criterion for the inter‐particle bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of bond thickness on the contact behaviour has been experimentally confirmed by Jiang et al (2014), indicating the need for a size-dependent bond contact law for a rigorous DEM analysis.…”
Section: Introductionmentioning
confidence: 91%
“…Because the stress distribution inside a bond is oversimplified, which in reality can be extremely complex , shortcomings in these criteria are obvious: bond geometry effects are not considered; compressive bond failure is usually ignored; and the normal force dependence of shear and rolling strengths (and torsion strength in three‐dimensional (3D) DEM) of a bond and their coupling is not well captured. All these aspects had been experimentally found to be significant .…”
Section: Introductionmentioning
confidence: 98%
“…In the authors' team, bond failure was studied in a series of two‐dimensional (2D) experiments on bonded aluminum rod doublets under various loading modes . The experimental results have been incorporated into a bond failure criterion to remedy the aforementioned shortcomings, thus leading to more realistic 2D DEM simulations .…”
Section: Introductionmentioning
confidence: 99%